Fungsi Hadis terhadap Al-Qur’an - Nur Azizah; Siti khalijah Simanjuntak; Sri Wahyuni (Jurnal Dirosah Islamiyah, 2023)
Writing this article aims to describe the function of the hadith on the Koran and what the scholars think about the function of the hadith in Islam. The existence of Hadith in people's lives becomes important if the Al-Quran does not provide a detailed explanation of a problem. The Al-Quran as the first source contains teachings that are mujmal or general and global in nature while the Hadith as the second source functions as an explanation for the generality of the contents of the Al-Quran. adis is the second source for Islamic laws, explaining everything that the Koran wants, as an explanatory, advisory, interpreter, tahsis, pentaqyid and who is responsible for the non-existent. The Qur'an and Hadith are life guidelines for their adherents, as sources of law and legal references in Islam, the two cannot be separated. In other words, hadith is the second source of Islamic law after the Koran. Hadith as an explanation (bayan) of the Koran has four kinds of functions, namely: First, Bayan al-taqrir is also called bayan al-ta'qid and bayan al-isbat, namely establishing and strengthening what has been explained in the Koran. Second, Bayan al-tafsir is a hadith function that provides details and interpretations of the verses of the Koran that are still global (mujmal), provides conditions or limitations (taqyid) of the verses of the Koran that are absolute, and specializes (takhshish) verses of the Koran that are still general. Third, Bayan at-tasyri' is realizing a law or teachings that are not found in the Koran or in the Koran there are only the main points. Fourth, Bayan at-nasakh, namely the abolition of the Syar'i law with a syar'i argument that came later. Keywords: Bayan Taqrir, bayan Bayan Tafsir, bayan Tasyri’, Bayan Nasakh